2014
DOI: 10.1007/s40553-014-0024-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ball Milling of Aluminum Powders in Promotion of Aluminum-Water Reaction to Generate Hydrogen

Abstract: Effect of ball milling (BM) of an aluminum powder on hydrogen generation through a reaction with hot water was investigated. BM increased surface area of the aluminum particles, increased crystalline imperfections in the aluminum lattice, and removed a native oxide film on surface of the particles. The increase in surface area of the particles was studied by measurement of particle size and examination of cross section of the particles. The effect of crystalline imperfections was studied by room temperature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Microsized Al powders were ball milled, and an optimal milling time was found to optimize both the lattice imperfections and the porosity of the microstructure and thus enhancing the yield of hydrogen produced when reacted with water . It was also found that the fine and deformed grains with more grain boundaries had more affinity for the reaction . Also, micro‐Al particles that were mechanically milled with micro‐NaCl particles formed an Al core and NaCl shell structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microsized Al powders were ball milled, and an optimal milling time was found to optimize both the lattice imperfections and the porosity of the microstructure and thus enhancing the yield of hydrogen produced when reacted with water . It was also found that the fine and deformed grains with more grain boundaries had more affinity for the reaction . Also, micro‐Al particles that were mechanically milled with micro‐NaCl particles formed an Al core and NaCl shell structure.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-Al particles form laminate structures 5 of Al (OH) 3 , whereas the nano-Al particles form highly porous fibrous spheres of AlOOH. 16 Furthermore, some methods such as mechanical activation 17,18 and protective salt layering 19 have been investigated to increase the reaction rates by optimizing the surface area at the Al/hydroxide interface and increasing the mass diffusion of H 2 O through the by-product shell. Microsized Al powders were ball milled, and an optimal milling time was found to optimize both the lattice imperfections and the porosity of the microstructure and thus enhancing the yield of hydrogen produced when reacted with water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] In the past few years, many methods have been developed to activate Al metal so that Al can directly react with water, e.g. using an alkaline solution, [6][7][8][9][10][11][12][13][14] alloying Al by doping with Ga, In, Bi, Sn, etc., [15][16][17][18][19][20][21][22][23] mechanically milling Al metal with special oxides and soluble inorganic salts, [24][25][26][27][28][29] mixing Al with alkaline chemicals, [30][31][32][33] ceramic oxide modication, etc. [34][35][36][37][38][39] For the above methods, however, the pollution concerns about alkaline solutions, the high price of rare metals, and the need for complicated activation procedures have set back the prospects for Al-hydrogen technology in commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, for production of nano-crystalline powders by severe plastic deformation where no reaction is involved, or for activating a powder product for a reaction, it is not straightforward to determine the needed minimum milling time. Accordingly, researchers introduced the "steady state time", which is defined as the milling time after which further milling has negligible effects on the powder products [1,[7][8][9][10][11][12]. Changes in size and shape of particles, preferred orientation and presence of lattice imperfections (e.g.…”
Section: Introductionmentioning
confidence: 99%